ANALISIS KERJASAMA SISWA PADA PEMBELAJARAN AKUNTANSI KELAS 12 MIA 4 SMA NEGERI - Puspita, Mega; Ulfah, Maria; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the clarity regarding the cooperation of students in accounting learning class XII MIA 4 Pontianak State High School 2. This research was stimulated by the issue that the development of student cooperation was not considered in formal education, in fact cooperation was very important and had become the demand of the 21st century education so that students were able to create reliable human resources, the sub-problems in this study were to find out about spontaneous cooperation , direct, and student contracts. The research method used is descriptive with a qualitative approach and the form of the survey research. The data sources in this study were all students of class XII MIA 4, amounting to 40 students and teachers who teach accounting. Data were collected using interview instruments and observation sheets, and using the technique of checking the validity of technical triangulation data, researchers conducted research 5 times, namely by conducting research observations as much as 3 times and interviews for 2 days. The results showed that student cooperation can be achieved by good is direct cooperation, while spontaneous collaboration and contracts are still not able to be achieved well by students. Keyword: Student Cooperation, Accounting Learning.